Characterization of a compact LaBr3(Ce) detector with Silicon photomultipliers at high 14 MeV neutron fluxes. (18th October 2017) - Rigamonti, D.; Nocente, M.; Giacomelli, L.; Tardocchi, M.; Angelone, M.; Broslawski, A.; Cazzaniga, C.; Figueiredo, J.; Gorini, G.; Kiptily, V.; Korolczuk, S.; Murari, A.; et al.
Abstract: A new compact gamma-ray spectrometer based on a Silicon Photo-Multiplier (SiPM) coupled to a LaBr_{3} 3 (Ce) crystal has been developed for the upgrade of the Gamma Camera (GC) of JET, where it must operate in a high intensity neutron/gamma-ray admixed field. The work presents the results of an experiment aimed at characterizing the effect of 14 MeV neutron irradiation on both LaBr_{3} 3 (Ce) and SiPM that compose the full detector. The pulse height spectrum from neutron interactions with the crystal has been measured and is successfully reproduced by MCNP simulations. It is calculated that about 8% of the impinging neutrons leave a detectable signal of which less than< 4 < 4 % of the events occur in the energy region above 3 MeV, which is of interest for gamma-ray spectroscopy applications. Neutron irradiation also partly degrades the performance of the SiPM and this is mostly manifested as an increase of the dark current versus the neutron fluence. However, it was found that the SiPM can be still operated up to a fluence of4×10^{10} 4×10 10 n/cm^{2} 2, which is the highest value we experimentally tested. Implications of these results for GC measurements at JET are discussed.